Coordination between vapor pressure deficit and CO2 on the regulation of photosynthesis and productivity in greenhouse tomato production - Jiao, Xiao-Cong; Song, Xiao-Ming; Zhang, Da-Long; Du, Qing-Jie; Li, Jian-Ming (Scientific reports, 2019)
The high vapor pressure deficit (VPD) in some arid and semi-arid climates creates undesirable conditions for the growth of tomato plants ( Solanum lycopersicum L., cv. Jinpeng). The global CO 2 concentration ([CO 2 ]) has also risen in recent years to levels above 400 μmol·mol −1 . However, the coordinated effect of VPD and [CO 2 ] on tomato plant growth remains unclear, especially at VPDs of 5–6 kPa or even higher that are extremely detrimental to plant growth. Here, we explore the interaction of VPD and [CO 2 ] on plant water status, stomatal characteristics, and gas exchange parameters in summer greenhouses in a semi-arid area. Plants were grown in four adjacent glass greenhouses with different environmental conditions: (i) high VPD + low [CO 2 ] representing natural/control conditions; (ii) high VPD + high [CO 2 ] representing enriched CO 2 ; (iii) low VPD + low [CO 2 ] representing reduced VPD; and (iv) low VPD + high [CO 2 ] representing reduced VPD and enriched CO 2 . Reducing the VPD alleviated the water stress of the plant and increased the gas exchange area of the leaf, which was beneficial to the entry of CO 2 into the leaf. At this time, the increase of [CO 2 ] was more beneficial to promote the photosynthetic rate and then improve the water use efficiency and yield.